Effects of voltage strength during electroporation on the development and quality of in vitro‐produced porcine embryos. (14th November 2017) - Nishio, K; Tanihara, F; Nguyen, T‐V; Kunihara, T; Nii, M; Hirata, M; Takemoto, T; Otoi, T
Contents: This study was conducted to determine suitable conditions for an experimental method in which the CRISPR/Cas9 system is introduced into in vitro‐produced porcine zygotes by electroporation. In the first experiment, when putative zygotes derived from in vitro fertilization (IVF) were electroporated by either unipolar or bipolar pulses, keeping the voltage, pulse duration and pulse number fixed at 30 V/mm, 1 msec and five repeats, respectively, the rate of blastocyst formation from zygotes electroporated by bipolar pulses decreased compared to zygotes electroporated by unipolar pulses. In the second experiment, the putative zygotes were electroporated by electroporation voltages ranging from 20 V/mm–40 V/mm with five 1‐msec unipolar pulses. The rate of cleavage and blastocyst formation of zygotes electroporated at 40 V/mm was significantly lower ( p  <   .05) than that of zygotes electroporated at less than 30 V/mm. Moreover, the apoptotic nuclei indices of blastocysts derived from zygotes electroporated by voltages greater than 30 V/mm significantly increased compared with those from zygotes electroporated by voltages less than 25 V/mm ( p  <   .05). When zygotes were electroporated with Cas9 mRNA and single‐guide RNA (sgRNA) targeting site in the FGF10 exon 3, the proportions of blastocysts with targeted genomic sequences were 7.7% (2/26) and 3.6% (1/28) in the embryos derived from zygotes electroporated at 25 V/mm and 30 V/mm, respectively. Our results indicate that electroporation at 25 V/mm may be an acceptable condition for introducing Cas9 mRNA and sgRNA into pig IVF zygotes under which the viability of the embryos is not significantly affected.